Experience with neuromuscular diseases at a high-complexitypediatric center in Peru: a seven-year retrospective study - Martinez, Peggy (2026)
Neuromuscular diseases (NMDs) are heterogeneous disorders of the motor unit characterized by variable onset and a progressive course, and their diagnosis is often delayed due to clinical and genetic diversity. The aim of this study was to describe the experience of the Instituto Nacional de Salud del Niño San Borja (INSNSB – San Borja National Institute of Child Health) in diagnosing genetically determined NMDs in a pediatric population. A descriptive retrospective study was conducted between January 2019 and June 2025. Cases were identified through review of clinical records and codes from the International Statistical Classification of Diseases and Related Health Problems, 10th Revision (ICD-10). Genetic diagnosis was established using neuromuscular gene panels, whole-exome sequencing (WES), multiplex ligation-dependent probe amplification (MLPA), and polymerase chain reaction (PCR) for the detection of spinal muscular atrophy (SMA). A total of 163 patients were included: 123 males (75.5%) and 40 females (24.5%). Primary muscle diseases were the most frequent group (54.5%), particularly Duchenne muscular dystrophy. Motor neuron diseases accounted for the second most frequent group (18.2%), followed by hereditary neuropathies, mainly Charcot–Marie–Tooth (CMT) disease. All identified variants corresponded tomonogenic disorders, with X-linked inheritance being the predominant pattern. In conclusion, this first descriptive study of genetic neuromuscular diseases in a Peruvian pediatric population highlights the need to strengthen early diagnosis, improve access to genetic testing, and reinforce referral networks in a context of increasing availability of disease-modifying therapies.